Aggregation, ratio variables, and measurement problems in criminological research - Parker, Robert Nash (Journal of quantitative criminology, 1985)
Issues of measurement error, level of aggregation, and ratio variables have been considered serious problems in criminological research. Although there have been many recent discussions of these issues in sociology and criminology, studies designed to assess the impact of these problems on the results of empirical research have, for the most part, been absent. After reviewing what is known theoretically and conceptually about these issues, an investigation which compares empirical analyses of a particular type of crime, homicide, that use different measurement strategies, different levels of aggregation, and ratio versus nonratio variables is presented. Utilizing homicide data from the mid-1970s and selected independent variables, the results of this investigation indicate that these three problems can interact in an empirical setting such that potential solutions to these problems do not always apply in the manner suggested in previous studies. The results also indicate that there is great risk in ignoring one or more of these problems in empirical research, in that different substantive conclusions can be reached from analyses that ignore these issues compared with analyses that deal directly with them.